A comparison of functional brain changes associated with surgical versus behavioral weight loss. (17th October 2013) - Bruce, Amanda S.; Bruce, Jared M.; Ness, Abigail R.; Lepping, Rebecca J.; Malley, Stephen; Hancock, Laura; Powell, Josh; Patrician, Trisha M.; Breslin, Florence J.; Martin, Laura E.; Donnelly, Joseph E.; Brooks, William M.; et al.
<x xml:space="preserve">Abstract</x> Objective Few studies have examined brain changes in response to effective weight loss; none have compared different methods of weight‐loss intervention. Functional brain changes associated with a behavioral weight loss intervention to those associated with bariatric surgery were compared. Design and Methods Fifteen obese participants were recruited prior to adjustable gastric banding surgery and 16 obese participants were recruited prior to a behavioral diet intervention. Groups were matched for demographics and amount of weight lost. Functional magnetic resonance imaging scans (visual food motivation paradigm while hungry and following a meal) were conducted before and 12 weeks after surgery/behavioral intervention. Results When compared to bariatric patients in the premeal analyses, behavioral dieters showed increased activation to food images in right medial prefrontal cortex (PFC) and left precuneus following weight loss. When compared to behavioral dieters, bariatric patients showed increased activation in bilateral temporal cortex following weight loss. Conclusions Behavioral dieters showed increased responses to food cues in medial PFC—a region associated with valuation and processing of self‐referent information—when compared to bariatric patients. Bariatric patients showed increased responses to food cues in brain regions associated with higher level perception—when compared to behavioral dieters. The method of weight loss determines unique changes in brain function.